2022
DOI: 10.51791/njap.v49i2.3476
|View full text |Cite
|
Sign up to set email alerts
|

Performance and meat attributes of finisher broiler chickens administered aqueous extracts of dried calyx from roselle plant (Hibiscus sabdariffa)

Abstract: The performance, carcass, organ characteristics and meat attributes of finisher broiler chickens administered varying concentrations of aqueous extract of dried calyx roselle plant were assessed in this study. Two hundred grams of dried calyx roselle plant was boiled in 2litres of water for 10 minutes to obtain the flower extract. After boiling, the extract was obtained with the aid of a syringe and was applied into a litre of drinking water at varying mls. The concentrations were 0, 5,10, 20, and 30 ml of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bayoub et al (2010) also found that the ethanol extract of cloves was the most potent against monocytogenes among other selected plant extracts. Akinduro et al (2020) reported no presence of salmonella specie in preserved broiler meat boiled with EP as spice after the third day of refrigeration. The report of Isikwenu and Udomah (2015) detailed that the dietary inclusion of EP reduces the bacterial load when added to broiler feed.…”
Section: Meat Microbiologymentioning
confidence: 98%
“…Bayoub et al (2010) also found that the ethanol extract of cloves was the most potent against monocytogenes among other selected plant extracts. Akinduro et al (2020) reported no presence of salmonella specie in preserved broiler meat boiled with EP as spice after the third day of refrigeration. The report of Isikwenu and Udomah (2015) detailed that the dietary inclusion of EP reduces the bacterial load when added to broiler feed.…”
Section: Meat Microbiologymentioning
confidence: 98%